Development of colour image processing and texture analysis method for medical endoscopic images - Wang, Peng. (2008)
The objective of this project is to develop a new technique for automated analysis of the colonoscopic images based on colour and texture information for cancer screening. The proposed method involves colonoscopic image processing for characterization by new texture-associated features.